2024
DOI: 10.1680/jgeot.21.00198
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory characterisation of the response of intact chalk to cyclic loading

Abstract: This paper reports the cyclic behaviour of chalk, which has yet to be studied comprehensively. Multiple undrained high-resolution cyclic triaxial experiments on low-to-medium density intact chalk, along with index and monotonic reference tests, define the conditions under which either thousands of cycles could be applied without any deleterious effect, or failure can be provoked under specified numbers of cycles. Intact chalk's response is shown to differ from that of most saturated soils tested under comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…Such a result is in contrast to what has been observed for other materials (e.g. [3]), for which a larger amplitude A causes a faster degradation. Viscous effects might explain the observed behaviour.…”
contrasting
confidence: 99%
“…Such a result is in contrast to what has been observed for other materials (e.g. [3]), for which a larger amplitude A causes a faster degradation. Viscous effects might explain the observed behaviour.…”
contrasting
confidence: 99%
“…The surrounding intact chalk provides stiff radial containment to the reconsolidated putty annuli formed around the pile shafts and constrains any dilation that develops as the putty fails monotonically or degrades under cycling. Ahmadi-Naghadeh et al (2022) investigated intact SNW chalk's undrained cyclic triaxial behaviour under in-situ stress conditions. High quality samples could withstand one-way deviator stress amplitudes, q cyc = Δσ 1 -Δσ 3 , up to 700 kPa in a fully stable manner.…”
Section: Monotonic and Cyclic Behaviour Of Snw Chalkmentioning
confidence: 99%
“…Cyclic loading was central to ALPACA. More than 20 locally instrumented cyclic triaxial tests were conducted on intact chalk specimens, which demonstrated a response more like that of crystalline rocks or metals than sedimentary soils (Ahmadi-Naghadeh et al, 2022). Noting that the near shaft, fully de-structured chalk, dominates axial capacity development in chalk, Liu et al (2022) conducted suites of locally instrumented monotonic and cyclic triaxial tests on chalk that had been de-structured by dynamic compaction at natural water content before re-consolidation to the conditions applying adjacent to the pile shafts.…”
Section: Snw Test Site Conditions and Chalk Characterization Studiesmentioning
confidence: 99%
“…describe also the monotonic and cyclic tests performed on the larger ALPACA Plus piles.10Dissemination of resultsThe ALPACA and ALPACA JIP results are being disseminated through a coordinated series of open access journal papers byAhmadi-Naghadeh et al (2022),Buckley et al (2020a), (2023),Jardine et al (2023),Liu et al (2022 andVinck et al (2023) and articles in international conferences, including OSIG-2023. Parallel studies at another chalk site are reported byVinck et al (2023);Pedone et al (2023) andWen et al (2023a, b) report on related advances in numerical analysis.…”
mentioning
confidence: 99%